Choephori - Aeschylus (Bloomsbury, 2016)
Aeschylus' famed tragedies 'Agamemnon', 'The Libation Bearers' and 'The Eumenides' comprise 'The Oresteia', which uses the story of a family curse and a long history of murder and revenge to raise haunting questions about the nature and the price of justice.
10.5040/9781784603496.00000017
Keywords: Drama; Aeschylus; Agamemnon; Orestes; Electra